Impact of aristolochic acid exposure on oncologic outcomes of upper tract urothelial carcinoma after radical nephroureterectomy - Zhong, Wenlong (Onco Targets Ther, 2017)
OBJECTIVE: To investigate the effect of aristolochic acids (AA) exposure, including exposure duration and years since last exposure, on oncologic outcomes of patients with upper tract urothelial carcinoma (UTUC) after radical nephroureterectomy (RNU). METHODS: We retrospectively collected clinicopathologic and AA exposure variables for 942 UTUC patients treated with RNU between 1999 and 2014 in a high-volume center of China. AA exposure duration was categorized as (>3 vs ≤3 years) and time since last AA exposure to surgery as (>5 vs ≤5 years). RESULTS: A total of 856 patients (90.9%) had none or possible AA exposure and 86 patients (9.1%) had credible AA exposure history. Among the 86 patients, 57 (66.3%) had AA exposure for ≤3 years and 29 (33.7%) had exposure for >3 years. The median follow-up duration was 60 months. By multivariate analysis, AA exposure history was significantly associated with cancer specific survival (hazard ratio [HR]: 0.43, p=0.02), intravesical recurrence (IVR) (HR: 2.25, p<0.001) and contralateral UTUC recurrence (HR: 2.71, p=0.001). After adjusted for the effects of standard clinicopathologic characteristics, exposure duration was independent risk factor for subsequent IVR (exposure duration ≤3 years vs none/possible AA, HR: 1.87, p=0.009; exposure duration >3 years vs none/possible AA, HR: 3.07, p<0.001), but not for cancer-specific survival (p=0.06). Also, of those patients who had AA exposure, those having exposure within 5 years prior to RNU did not differ from patients having last exposure >5 years ago regarding cancer specific mortality (p=0.67) and IVR (p=0.54). CONCLUSION: AA exposure was associated with worse cancer-specific survival, higher rate of IVR and contralateral UTUC recurrence of UTUC treated with RNU. The association between AA exposure and IVR seems to be time-dependent. Exposure cessation >5 years prior to RNU cannot mitigate the impact of AA on the UTUC prognosis.